Decision-Making Tool for Knowledge-Based Projects in Offshore Production Systems - Serapiao, Adriane Beatriz de S. [UNESP]; Mendes, Jose R. P.; Morooka, Celso K. (Springer-verlag Berlin, 2012)
The development of an offshore field demands knowledge of many experts to choose the different components of an offshore production system. All the specialized parts of this knowledge are intrinsically related. The aim of this paper is to use Fuzzy Sets and knowledge-based systems to describe and formalize the phases of development of an offshore production system project, in order to share and to manage the required knowledge for carrying out a project, while at the same time proposing alternatives for the oil field configuration.
Keywords: offshore production system; petroleum engineering; decision-making tool; knowledge-based system; fuzzy system